PHILOSOPHICAL ANTHROPOLOGY, ETHICS, AND LOVE: TOWARD A NEW RELIGION AND SCIENCE DIALOGUE: with Pat Bennett and John A. Teske, "The Road Is Made by Walking: An Introduction"; J. Wentzel van Huyssteen, "Can We Still Talk about 'Truth' and 'Progress' in Interdisciplinary Thinking Today?"; Jonathan Marks, "What If the Human Mind Evolved for Nonrational Thought? An Anthropological Perspective"; Phillip Cary, "Right‐Wing Postmodernism and the Rationality of Traditions"; Margaret Boone Rappaport and Christopher Corbally, "Human Phenotypic Morality and the Biological Basis for Knowing Good"; Christian Early, "Philosophical Anthropology, Ethics, and Love: Toward a New Religion and Science Dialogue"; Warren S. Brown, "Knowing Ourselves as Embodied, Embedded, and Relationally Extended"; and John A. Teske, "Knowing Ourselves by Telling Stories to Ourselves.". Issue 3 (September 2017) - Early, Christian
Abstract: Religion and science dialogues that orbit around rational method, knowledge, and truth are often, though not always, contentious. In this article, I suggest a different cluster of gravitational points around which religion and science dialogues might usefully travel: philosophical anthropology, ethics, and love. I propose seeing morality as a natural outgrowth of the human desire to establish and maintain social bonds so as not to experience the condition of being alone. Humans, of all animals, need to feel loved—defined as a compassionate present‐with in dynamic dyadic relation such that one experiences the sense of mattering—but that need has an equally natural tendency to be met by creating biased us‐and‐them distinctions. A "critical" natural ethics, then, is one in which we become aware of and work to undermine our tendency to reify in‐group distinctions between "us" and "them." Religious communities that work intentionally on this can be seen, to some extent, as laboratories of love—or as sites for co‐creating knowledge in perilous times.